A COMPREHENSIVE LITERATURE REVIEW ON TIME VALUE OF MONEY AND ECONOMIC VALUE OF TIME FOR FINANCIAL DECISION-MAKING - Lahuri, Setiawan bin; Wardani, Baiq Alfina Rahma; Zuhroh, Ainun Amalia (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2025)
This study aims to analyze the concept of economic value of time as an answer to the distractions concept of time value of money by conventional views. The significance of comprehending the distinction between the temporal value of money and the economic value of time for the Muslim community to prevent entrapment in usurious transactions. Money in the conventional impacted to the continuous passage of time which requires an increase in face value to increase. This concept is referred to as the time value of money. As a result, this concept is related to the concept of discounting which in reality indirectly associates itself with the term